2017
DOI: 10.1016/j.socscimed.2017.08.034
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Black cancer patients' race-related beliefs and attitudes on racially-discordant oncology interactions: A field study

Abstract: Objective Both physician and patient race-related beliefs and attitudes are contributors to racial healthcare disparities, but only the former have received substantial research attention. Using data from a study conducted in the Midwestern US from 2012 to 2014, we investigated whether 114 Black cancer patients’ existing race-related beliefs and attitudes would predict how they and 18 non-Black physicians (medical oncologists) would respond in subsequent clinical interactions. Method At least two days before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…These low means may be unique to our sample: physicians in our sample have elected to work in a city with a majority Black population; patients with high levels of mistrust and perceived discrimination may not have consented to participate in the study. However, it is worth noting that race-related attitudes did predict post-visit impressions in the current analyses, and that past work with the same patient and physician populations has found consistent relationships between race-related attitudes and post-visit impressions as well as other behaviors during interactions (Penner et al, 2016a,b, 2017). If the lack of relationship between race-related attitudes and affective behavior is replicated in future work, it may be that these attitudes influence impressions through other kinds of nonverbal behavior.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…These low means may be unique to our sample: physicians in our sample have elected to work in a city with a majority Black population; patients with high levels of mistrust and perceived discrimination may not have consented to participate in the study. However, it is worth noting that race-related attitudes did predict post-visit impressions in the current analyses, and that past work with the same patient and physician populations has found consistent relationships between race-related attitudes and post-visit impressions as well as other behaviors during interactions (Penner et al, 2016a,b, 2017). If the lack of relationship between race-related attitudes and affective behavior is replicated in future work, it may be that these attitudes influence impressions through other kinds of nonverbal behavior.…”
Section: Discussionsupporting
confidence: 48%
“…Patients and physicians enter clinic visits already holding attitudes and beliefs that can impact their impressions and decisions. For example, Black patients’ mistrust of the healthcare system is related to confidence in treatment recommendations (Penner et al, 2017), engagement in genetic counseling (Sheppard et al, 2013), and quality of life (Kinlock et al, 2017). Physicians’ biases and stereotypes can guide their impressions and treatment recommendations (Penner et al, 2014; van Ryn et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There exists a body of literature regarding the experience of Black patients in the health care system, where a history of medical distrust and ineffective patient‐provider communication can have significantly negative impacts on patients' care 25,26 . Such impacts have been found to be particularly magnified in race‐discordant clinical interactions, and prior work has shown that pre‐existing race‐related beliefs can have significant negative effects on a patients' perception of recommended treatment difficulty and treatment efficacy 27 . Our findings may reflect such race‐related effects.…”
Section: Discussionmentioning
confidence: 99%
“…Our prior research suggests such perceptions and behaviours are associated with less positive patient expectations about recommended treatments 51. We have also found that black patients with higher levels of suspicion of medical care are less optimistic about outcomes of recommended treatments and are perceived by their physicians to be less educated 52. This, in turn, is associated with less positive physician expectations about how their black patients will do on a treatment protocol, such as their adherence and/or ability to tolerate treatment.…”
Section: Introductionmentioning
confidence: 85%